PELAKSANAAN UPACARA ADAT PERKAWINAN DAYAK PESAGUAN KAWIN JADIK SUNTUNG DI DESA AUR GADING KECAMATAN TUMBANG TITI KABUPATEN KETAPANG - NIM. A1012221121, JOSAFAT PUTRA BUNGAS (Fakultas Hukum Universitas Tanjungpura, 2026)
Abstract The Dayak Pesaguan community, practicing the Jadik Suntung marriage ceremony in Aur Gading Village, adheres to customary law, one of which is the marriage tradition, which is still adhered to and practiced today. Marriage customs are ancestral traditions that are still practiced from generation to generation. However, over time, the Dayak Pesaguan community, practicing the Jadik Suntung marriage ceremony in Aur Gading Village, Tumbang Titi District, Ketapang Regency, has stopped practicing traditional marriages according to their original customs. The research question is,